PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG PROLIFIK PADA BERBAGAI JARAK TANAM DALAM BARIS DENGAN SISTEM TANAM JAJAR LEGOWO - Intan Dwi Lestari (Percetakan Umi Toaha Makassar, 2020)
This research aimed to determine the effect of spacing on the growth and yield of corn. It was conducted from July to November 2019 at the Experimental Plantation of Cereal Crops Research Institute (BalitSereal), Maros, South Sulawesi. The experimental method used was a randomized block design consisting of 4 treatments: J1= (100 cm x 50 cm) x 20 cm, one seed per hole; J2= (100 cm x 50 cm) x 30 cm, alternating between one seed per hole and two seeds per hole; J3= (100 cm x 50 cm) x 40 cm, two seeds per hole; J4= (100 cm x 50 cm) x 15 cm, one seed per hole. The observed variables were plant height, number of leaves, stem diameter, leaf area index, Anthesis Silking Interval (ASI), length of cob 1 and cob 2, diameter of cob 1 and cob 2, weight of shelled seeds/plant, weight of 100 seeds on cob 1 and cob 2, and production of shelled seeds/hectare. The experimental results showed that plant spacing affected the growth and production of maize. The J3 spacing (100 cm x 50 cm) x 40 cm with two seeds per hole significantly affected the leaf area index and gave the highest average stem diameter. The J2 spacing with (100 cm x 50 cm) x 30 cm with alternating between one seed per hole and two seeds per hole produced the highest production in terms of weight of shelled seeds/plant, weight of 100 seeds and yield of shelled seeds/hectare.